Taxation on mining and hydrocarbon investments - Vega Rengifo, Beatriz de la (2014)
This article comments the most important aspects of the tax treatment applicable to investments of mining and oil and gas industry. The document highlights the relevant tax topics of the general tax legislation(Income Tax Law) and the special legislation of both industries (General Mining Law and Hydrocarbons Organic Law).